Genetic Study of Suppressor-Sensitive Mutants of the Bacillus subtilis Bacteriophage φ29 - Reilly, Bernard E. (1973)
With bacteriophage φ29 of Bacillus subtilis 133, suppressor-sensitive (sus) hydroxylamine mutants have been isolated. Intracistronic and intercistronic quantitative complementation placed the mutants in 13 cistrons, and three-factor crosses have been used to assign an unambiguous order for 10 cistrons. Recombination frequencies have been presented for several regions of the genome to facilitate comparison of the sus system with the previously published temperature-sensitive mapping systems.